2013
DOI: 10.1055/s-0033-1335044
|View full text |Cite
|
Sign up to set email alerts
|

Erstmanifestation eines organischen manisch-schizophreniformen Syndroms mit nachfolgender Katatonie bei NMDA-Rezeptor-Antikörper-positiver Encephalitis

Abstract: We report on a 39-year-old female patient who developed catatonia after there had been schizomanic symptoms in the six months before. At admission the patient exhibited catatonia, a tetraspastic syndrome and focal epileptic seizures. The cranial MRI revealed bilateral subcortical hyperintense lesions which took up contrast agent. Examination of the cerebrospinal fluid disclosed a lymphocytic pleocytosis and autochthone oligoclonal bands. In the serum autoantibodies against the NMDA-NR-1 receptor were reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Schizophreniform psychosis is a frequent phenomenon and has been supported by a recent study of a 60-patient cohort of patients suffering first-episode psychosis and additional neurological features such as seizures or autonomic symptoms [27% of these patients had been diagnosed with NMDAR encephalitis] (Tang et al 2019). The complex psychiatric presentation of NMDAR encephalitis was enriched in subsequent years to incorporate bipolar mood dysfunction and mania (Choe et al 2013;Fousse et al 2013), anxiety (Maat et al 2013) and behavioral abnormalities including agitation (Maat et al 2013). Psychotic and depressive syndrome often coexist, as reported by a large-scale study of Al-Diwani et al (2019) including 505 patients reported with psychiatric symptomatology in NMDAR encephalitis.…”
Section: Nmdar Antibody-positive Encephalitismentioning
confidence: 97%
“…Schizophreniform psychosis is a frequent phenomenon and has been supported by a recent study of a 60-patient cohort of patients suffering first-episode psychosis and additional neurological features such as seizures or autonomic symptoms [27% of these patients had been diagnosed with NMDAR encephalitis] (Tang et al 2019). The complex psychiatric presentation of NMDAR encephalitis was enriched in subsequent years to incorporate bipolar mood dysfunction and mania (Choe et al 2013;Fousse et al 2013), anxiety (Maat et al 2013) and behavioral abnormalities including agitation (Maat et al 2013). Psychotic and depressive syndrome often coexist, as reported by a large-scale study of Al-Diwani et al (2019) including 505 patients reported with psychiatric symptomatology in NMDAR encephalitis.…”
Section: Nmdar Antibody-positive Encephalitismentioning
confidence: 97%